Electron diffraction study of the sillenites Bi12SiO20, Bi25FeO39 and Bi25InO39: Evidence of short-range ordering of oxygen-vacancies in the trivalent sillenites - Craig A. Scurti; Nicolas Auvray; Michael W. Lufaso; Seiji Takeda; Hideo Kohno; D. J. Arenas (AIP Advances, 2014)
We present an electron diffraction study of three sillenites, Bi12SiO20, Bi25FeO39, and Bi25InO39 synthesized using the solid-state method. We explore a hypothesis, inspired by optical studies in the literature, that suggests that trivalent sillenites have additional disorder not present in the tetravalent compounds. Electron diffraction patterns of Bi25FeO39 and Bi25InO39 show streaks that confirm deviations from the ideal sillenite structure. Multi-slice simulations of electron-diffraction patterns are presented for different perturbations to the sillenite structure - partial substitution of the M site by Bi3+, random and ordered oxygen-vacancies, and a frozen-phonon model. Although comparison of experimental data to simulations cannot be conclusive, we consider the streaks as evidence of short-range ordered oxygen-vacancies.